Employment Sustainability and Prospects of the Automotive Industry in Saudi Arabia - Yusuf, Nadia; Nasrulddin, Vivian (European Journal of Sustainable Development, 2021)
The research revolves around the automotive industry of Saudi Arabia and how the industry can be used as an opportunity towards creating more employment opportunities for the youth. A detailed discussion has been done to identify the existing problems in the concerned sector along with a brief background study. The employment opportunities and related trade conditions are also discussed. The growth prospects of the automotive industry along with the investment opportunities have been provided. In the later part of the research, recommendations for overall industry growth are mentioned. The report also contains references from reputed authors and trusted sources, which makes the report more authentic and informative. Detailed evaluation of the obtained data shows that changes in import and export rates can influence the employment market in terms of generating trade volume. Moreover, attempt to attract foreign investment through encouraging trade transactions can result in strengthening industrial growth through creating better employment opportunities.